Comparative bibliometric analysis of fertility preservation - Yildirim, Engin; Demir, Emre (Annals of Medical Research, 2021)
Aim: Fertility preservation (FP) has become an important issue for both women and men, due to oncological therapies, gonadotoxic treatments, surgeries, and infertility. The aim of this study is to investigate the publications related to FP, identify the top effective countries and journals, top productive researchers, and trend topics. Material and Methods: The data of this study were obtained using the Thomson Reuters WoS (Thomson Reuters, New York, NY, USA) database, separately for females and males. In the bibliometric analysis, ‘fertility preservation’ was used as a keyword. VOSviewer (Version 1.6.6) was utilized for bibliometric network visualizations. SPSS was used for the statistical analyses (Version 22.0)Results: Analysis results of the keywords used for men indicated 817 publications and for females indicated 2531 publications totally. The United States of America (USA) was the top country for the publications about both genders. The top three research fields for both genders were Obstetrics and Gynecology, Reproductive Biology, and Oncology. The journals that contributed to the literature most were Fertility and Sterility and Human Reproduction respectively in both gender categories. The correlation between the number of total fertility preservation articles and total cancers,Gross Domestic Product-World Bank (GDP-WB), Gross Domestic Product-International Monetary Fund (GDP-IMF), Human Development Index (HDI), and Internet Users (IU) was significant (r=0.482, p=0.017; r=0.609, p0.001; r=0.620, p0.001; r=0.365, p=0.043; r=0.479, p=0.006). Conclusion: It has been determined that researches on the protection of the fertility of cancer patients and infertile patients have increased from past to present. Also, it is observed that the economies of countries have an active role in research productivity.Keywords: Bibliometrics; fertility preservation; female; male.